Profylaktiska åtgärder för kaniner - Engström, Sandra (SLU/Dept. of Animal Environment and Health (until 231231), 2013)
Rabbits, Oryctolagos cuniculus, rapidly increases as pets. During the right circumstances, rabbits are friendly, social and playful. A rabbit who shows an abnormal behavior should always be examined by a veterinary, though there is almost always a medical problem.